A Profile of Reflective Literacy Among Seventh-Grade Middle School Students in Solving Mathematical Problems - Gustina Nandari Nandari; Yulia Pratiwi; Niki Pujarwati; Agung Putra Wijaya; Nurhanurawati (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2026)
This study aims to describe the reflective literacy profile of seventh-grade junior high school students in solving mathematical problems on the topic of data presentation by analyzing three main indicators: reacting (understanding problem information), comparing (connecting information with mathematical concepts and selecting strategies), and contemplating (monitoring problem-solving steps and evaluating final answers). A quantitative descriptive design was employed, involving 32 students and a 10-item essay instrument tested for validity and reliability. Results show an average reflective literacy score of 31.00, classified as moderate, with 15.63% of students in the high category, 59.38% in the moderate category, and 25.00% in the low category. Indicator analysis revealed the highest achievement in reaction (64.58%), followed by comparing (62.08%) and contemplating (60.00%), indicating that evaluation and monitoring skills still require improvement. These findings suggest the need for mathematics instruction emphasizing reflective activities, such as metacognitive questioning, reflection journals, group discussions, self-assessment, and answer review, to enable students to better understand, manage strategies, monitor processes, and evaluate solutions effectively.